Paroxysmal Sympathetic Hyperactivity – An Under-Recognized Entity in Pediatric Brain Tumors: Case Report and Review of Literature - Krishnan, Yamini; Smitha, B; Cholayil, Shamsudheen (Indian Journal of Medical and Paediatric Oncology, 2020)
Paroxysmal sympathetic hyperactivity (PSH) is not a well-recognized syndrome in pediatric brain tumors, but has been described in adults with traumatic brain injury. We describe the case of a child with medulloblastoma presenting with PSH. An index of suspicion is important in early diagnosis of PSH and this ultimately has an impact on the long-term outcome of patients with the syndrome.
Keywords: Dysautonomia; Medulloblastoma; paroxysmal sympathetic hyperactivity; Pediatric brain tumors